2021
DOI: 10.1021/acs.jpcc.0c11082
|View full text |Cite
|
Sign up to set email alerts
|

Improving Computational Assessment of Porous Materials for Water Adsorption Applications via Flat Histogram Methods

Abstract: Water adsorption in porous materials has recently drawn considerable attention for its tremendous potential in environmental applications such as water harvesting from air. A key step to the deployment of such technologies is the selection of optimal adsorbent materials as material performance directly impacts their efficiency. Owing to the vast materials space, computational studies may play a critically important role in facilitating the selection of the best material. The current state-ofthe-art method to p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
49
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 23 publications
(51 citation statements)
references
References 76 publications
2
49
0
Order By: Relevance
“…36,41,75,76 However, this approach might not be well-suited to study water adsorption because the cluster formation traps the system in local free energy minima, resulting in inadequate sampling of the phase space and an inability to reach the true equilibrium loading values. This was discussed in a previous study, 53 and the slow convergence of the GCMC simulations for water adsorption has also been reported in several prior studies. 36,41 In this study, we further probe the suitability of the GCMC method by applying it to simulate the condensation of the bulk water phase (i.e., reproduce the vapor liquid equilibrium of water).…”
Section: Suitability Of the Gcmc Methodssupporting
confidence: 66%
See 4 more Smart Citations
“…36,41,75,76 However, this approach might not be well-suited to study water adsorption because the cluster formation traps the system in local free energy minima, resulting in inadequate sampling of the phase space and an inability to reach the true equilibrium loading values. This was discussed in a previous study, 53 and the slow convergence of the GCMC simulations for water adsorption has also been reported in several prior studies. 36,41 In this study, we further probe the suitability of the GCMC method by applying it to simulate the condensation of the bulk water phase (i.e., reproduce the vapor liquid equilibrium of water).…”
Section: Suitability Of the Gcmc Methodssupporting
confidence: 66%
“…Indeed, we found in our previous study that water adsorption simulations in MOF-806 using GCMC also showed a large hysteresis loop which reduced in size as the number of cycles increased, but even after running several million cycles requiring months of computational time, the loop still existed. 53 By contrast, the NVT + W method is able to provide a single vapor-liquid equilibrium curve and shows the step to be at pressure ~4500 Pa which resembles the reported benchmark saturation pressure for the TIP4P model, 72 indicating much improved sampling (Figure 1A). Moreover, it converges within a few days of computational time, indicating more effective sampling.…”
Section: Suitability Of the Gcmc Methodsmentioning
confidence: 80%
See 3 more Smart Citations